Subjective discomfort in children receiving 3 T MRI and experienced adults' perspective on children's tolerability of 7 T: a cross-sectional questionnaire survey. Issue 10 (15th October 2014) - Chou, I-Jun; Tench, Christopher R; Gowland, Penny; Jaspan, Tim; Dineen, Rob A; Evangelou, Nikos; Abdel-Fahim, Rasha; Whitehouse, William P; Constantinescu, Cris S
Abstract : Objectives: To explore the possible discomfort perceived by children participating in 7 T MRI research, and the age range in which children are most likely to tolerate it well. Design: A cross-sectional survey using age-appropriate questionnaires containing six measures of subjective discomfort (general discomfort, dizziness, noisiness, claustrophobia and feeling of cold or warm). Setting: For children, 3 T clinical scanner in a tertiary referral teaching hospital; for adults, 3 and 7 T scanner in a university research building. Participants: Non-sedated children and young people under 18 years of age who underwent 3 T clinical MRI for brain or musculoskeletal scans and adult volunteers attending 7 T with or without 3 T for brain scans. Results: 83% (89/107) of involved individuals returned questionnaires. The most common discomfort among 31 children receiving 3 T MRI was noisiness (39%), followed by cold (19%), general discomfort (16%), dizziness (13%) and claustrophobia (10%). The noise was reported more frequently in children younger than 12 years than those older (p=0.021). The most common discomfort for 58 adults receiving 7 T MRI was noisiness (43%). In adults, there was a higher frequency of general discomfort during 7 than 3 T scans (p=0.031). More than 85% of adult respondents thought children aged 12–17 years would tolerate 7 T scans well, but only 35% and 15% thought children aged 10–11 and 8–9 years, respectively, would. Conclusions: Noisiness was the most common discomfort across all ages in 3 and 7 T scanners. Although general discomfort was more common during 7 than 3 T scans in adults, most adults thought children aged 12 years or more would tolerate 7 T MRI well. Cautious enrolment of children in 7 T MRI study is warranted, but until there is more evidence of how well those aged 12 years or more tolerate 7 T MRI, we would caution against enrolling younger children.